Approaching Porter's five forces through social media analytics. (11th October 2022) - Kumar, Vikas; Nanda, Pooja
As a result of increase in social media platforms and users, the need for tracking, collecting, analysing and reporting the data generated on these platforms has also increased. Businesses are rapidly using knowledge from social networks to provide resources, connect with their customers, and make strategic decisions for their companies. Present work explores how social media platforms can be used to support the decision making process in the organisations and in particular to achieve the competitive advantage. Porter's five forces model has been mapped to consider the impact of different forces and how the social media analytics can be used to tackle these. Social media analytics based strategic decisions have been considered, using the most commonly used analytics tools by industry (both proprietary and open source). Five most prevalent social media platforms (Facebook, LinkedIn, YouTube, Instagram and Twitter) have been taken for this study.